Effects of Hydrogen Peroxide Stress on the Nucleolar Redox Environment and Pre-rRNA Maturation - Sapio, Russell T.; Burns, Chelsea J.; Pestov, Dimitri G. (Frontiers in Molecular Biosciences, 2021)
Identifying biologically relevant molecular targets of oxidative stress may provide new insights into disease mechanisms and accelerate development of novel biomarkers. Ribosome biogenesis is a fundamental prerequisite for cellular protein synthesis, but how oxidative stress affects ribosome biogenesis has not been clearly established. To monitor and control the redox environment of ribosome biogenesis, we targeted a redox-sensitive roGFP reporter and catalase, a highly efficient H2O2 scavenger, to the nucleolus, the primary site for transcription and processing of rRNA in eukaryotic cells. Imaging of mouse 3T3 cells exposed to noncytotoxic H2O2 concentrations revealed increased oxidation of the nucleolar environment accompanied by a detectable increase in the oxidative damage marker 8-oxo-G in nucleolar RNA. Analysis of pre-rRNA processing showed a complex pattern of alterations in pre-rRNA maturation in the presence of H2O2, including inhibition of the transcription and processing of the primary 47S transcript, accumulation of 18S precursors, and inefficient 3'-end processing of 5.8S rRNA. This work introduces new tools for studies of the redox biology of the mammalian nucleolus and identifies pre-rRNA maturation steps sensitive to H2O2 stress.